Shear Strength of an Expansive Overconsolidated Clay Treated with Hydraulic Binders - Mahamedi, Abd elkrim (Université de M'sila, 2017)
This paper presents and analyzes the results of a series of identification; compaction and direct shear tests performed in accordance with the Algerian standards on expansive overconsolidated clay treated with locally manufactured hydraulic binders (composed Portland cement and extinct lime). This clay comes from the urban site of Sidi-Hadjrès city (wilaya of M'sila, Algeria), where significant damages frequently appear in the road infrastructures, roadway systems and various networks and in civil and industrial light structures. Tests results show that the geotechnical parameters deduced from these tests are concordant and confirm the shear strength improvement of this natural clay treated with cement or lime and compacted under the optimum Proctor conditions. However, contrary to its mineralogical characteristics which do not seem to be affected by the treatment, this expansive natural clay is characterized by as well drained as undrained shear strength sensitive to stabilizer content; the best performances are obtained for a treatment corresponding to 8% cement or lime content Cet article présente et analyse les résultats d'une série d'identifications; essais de compactage et de cisaillement direct effectués selon les normes algériennes sur une argile expansive surconsolidée traitée aux liants hydrauliques fabriqués localement (ciment Portland composé et chaux éteinte). Cette argile provient du site urbain de la ville de Sidi-Hadjrès (wilaya de M'sila, Algérie), où des dégâts importants apparaissent fréquemment dans les infrastructures routières, voiries et réseaux divers, ainsi que dans les constructions légères civiles et industrielles. Les résultats d’essais obtenus montrent que les valeurs des paramètres géotechniques déduits de ces essais sont concordantes et confirment l'amélioration de la résistance au cisaillement de cette argile naturelle traitée au ciment ou à la chaux et compactée dans les conditions Proctor optimales. Cependant, contrairement à ses caractéristiques minéralogiques qui ne semblent pas affectées par le traitement, cette argile naturelle expansive est caractérisée par une résistance au cisaillement aussi drainée que non drainée sensible à la teneur en stabilisant; les meilleures performances
Keywords: Expansive clay, Treatment, Hydraulic binders, Shear strength